2016
DOI: 10.1001/jamafacial.2015.1339
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Concussion in Patients With Isolated Mandible Fractures

Abstract: IMPORTANCEThis study examines the association between isolated mandible fractures and mild traumatic brain injury (mTBI).OBJECTIVE To determine the rates of mTBI in patients who have sustained isolated mandible fractures. DESIGN, SETTING, AND PARTICIPANTSA prospective study was conducted among patients who sustained isolated mandible fractures within 24 hours of presentation. Patients were administered the Military Acute Concussion Evaluation (MACE). Recorded data included demographics, time since injury, use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Because of the structure and anatomic proximity of the mandible as well as its direct connection to the skull base, trauma to the mandible is related to intracranial injury, and traumatic brain injuries were observed in 19% of trauma patients with mandibular fractures [ 20 ]. A 75% (12 of 16) rate of concussions associated with isolated mandible fracture has been reported [ 21 ]. Similarly, closed head injury has been identified in 32.4% of patients with mandible fractures caused by motor vehicle accidents [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the structure and anatomic proximity of the mandible as well as its direct connection to the skull base, trauma to the mandible is related to intracranial injury, and traumatic brain injuries were observed in 19% of trauma patients with mandibular fractures [ 20 ]. A 75% (12 of 16) rate of concussions associated with isolated mandible fracture has been reported [ 21 ]. Similarly, closed head injury has been identified in 32.4% of patients with mandible fractures caused by motor vehicle accidents [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries, traffic accidents are the main cause of mandibular fractures, however, interpersonal violence and physical assault are the most common cause of this kind of fracture in developed countries 8,9 . In the United States, the most frequent cause of mandible fractures is motor vehicle accidents and interpersonal violence 10 . Jaw fractures can occur alone or along with other facial bone fractures 11 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature focusing on the association of facial injuries and the mild type of TBI is limited. A recent publication showed that 75% (12 of 16 patients) of isolated mandible fractures were associated with cerebral concussion or mild TBI . Mild traumatic brain injury (mTBI) is defined by the American Academy of Neurology (1997) as “trauma‐induced alteration in mental status that may or may not involve loss of consciousness.” The clinical features may include: loss of consciousness, loss of memory before or after the accident, alteration in mental state and focal neurological deficit(s)…”
Section: Introductionmentioning
confidence: 99%
“…Despite the detrimental complications, the literature indicates that mTBI injuries are often left unreported or underdiagnosed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation